2005
DOI: 10.1136/bmj.331.7531.1545
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: the elephant in the corner

Abstract: In 2055, everybody knew that obesity was a problem, but what did they do about it?The year is 2055. Socrates is discussing the history of the western obesity epidemic with Panacea, the goddess of healing.Socrates: Do you recall the days when people were still allowed to smoke? Panacea: Indeed, Socrates. It seems unthinkable now. Of course in those days smoking was the leading preventable cause of chronic disease. It is remarkable how times have changed.Socrates: In the past 50 years, obesity has come to accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Adiposity is promoted at an individual level, as a reevaluation of the Framingham Heart Study suggested that the risk of becoming obese increased if a person had a close friend or spouse that was obese [23]. Society also probably promotes obesity in more subtle ways by promoting unhealthy lifestyles and limiting the choice for day-to-day aerobic exercise [24,25]. A European study, for example, reported lower obesity rates in pleasant areas with lots of greenery and low levels of litter and graffiti [26].…”
Section: Epidemiology Of the Causes Of Obesitymentioning
confidence: 98%
“…Adiposity is promoted at an individual level, as a reevaluation of the Framingham Heart Study suggested that the risk of becoming obese increased if a person had a close friend or spouse that was obese [23]. Society also probably promotes obesity in more subtle ways by promoting unhealthy lifestyles and limiting the choice for day-to-day aerobic exercise [24,25]. A European study, for example, reported lower obesity rates in pleasant areas with lots of greenery and low levels of litter and graffiti [26].…”
Section: Epidemiology Of the Causes Of Obesitymentioning
confidence: 98%
“…This moralising language is grounded in the assumption that the management of body size is within the remit of the individual and that the work of disciplining the body and its size constitutes a moral obligation (see, for example, Ebbeling et al, 2002;Ogilvie & Hamlet, 2005;Burry, 1999). One consequence is that clinical interventions that appear to relieve individuals of that responsibility-for example, drugs and surgery-are easily designated by critical others, through the mobilisation of well-established discourses of individual responsibility, as 'cheating'.…”
Section: Weight Loss 'Cheating'mentioning
confidence: 99%
“…This can only increase the urgency to identify effective treatments. Behavioural treatments that focus on helping people to control exposure to cues that trigger eating and to monitor and modify their behaviour have had consistent but modest success and are recognized to be most effective, apart from the drastic option of bariatric surgery (25). Drug treatments have not proved to be the promised panacea, but it is likely that treatments of the future are going to come from combining behavioural and pharmaceutical interventions, probably also taking into account genetic and behavioural differences.…”
Section: Future Directions For Behavioural Research Into Weight Controlmentioning
confidence: 99%